What a Painfully Interesting Subject: Charles Darwin’s Studies of Potato Late Blight - RISTAINO, JEAN BEAGLE; PFISTER, DONALD H. (Bioscience, 2016)
Charles Darwin’s famous voyage on the HMS Beagle led him around the world on a collecting journey that culminated in his theory of evolution. In 1835, the Beagle traveled to the island of Chiloé, and there, Darwin discovered and sent potatoes back to England. Darwin’s interest in the potato and potato late blight spanned four decades. He used the potato to investigate questions of what a species is, understand its ravages by a plant pathogen, and investigate ideas on clonal versus sexual reproduction on species fitness. Darwin’s letters reveal his thoughts on free trade, population growth and food security during the Irish famine. Darwin was involved in the first research to find resistance to late blight and personally funded a breeding program in Ireland. Here, we discuss Darwin’s studies on potato late blight and its relevance today in studies of global migrations of the pathogen and development of durable resistance.